2023
DOI: 10.35723/ajie.v7i1.382
|View full text |Cite
|
Sign up to set email alerts
|

Child-Friendly Islamic Boarding School (CFIBS): Realizing Humanistic Goals of Islamic Education

Abstract: Child-Friendly Islamic Boarding Schools (CFIBS) have emerged as a forum for realizing Islamic education's humanistic goals, especially in educating and caring for students. Proper and correct education and upbringing dramatically determine the quality of individuals who are not only intellectually intelligent but also have noble attitudes and behaviour. This study aims to analyze the model of protecting children from violence carried out by the IMMIM Islamic Boarding School and the Nahdlatul 'Ulum Makassar Isl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…Islam historically exemplified peaceful coexistence with other religions, emphasizing honesty, love, and tolerance, as seen in the respectful treatment of Jews and Christians [30]. Despite challenges, Muslims are encouraged to leverage the inherent value of tolerance within Islam to promote peacebuilding within and between faiths, emphasizing the need for dialogue, education, and community engagement to foster mutual respect and understanding [31]- [33].…”
Section: Discussionmentioning
confidence: 99%
“…Islam historically exemplified peaceful coexistence with other religions, emphasizing honesty, love, and tolerance, as seen in the respectful treatment of Jews and Christians [30]. Despite challenges, Muslims are encouraged to leverage the inherent value of tolerance within Islam to promote peacebuilding within and between faiths, emphasizing the need for dialogue, education, and community engagement to foster mutual respect and understanding [31]- [33].…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown a positive relationship between the availability of educational resources and student achievement (Requia & Silva, 2023). In rural areas, the condition of educational facilities becomes very important because schools often face infrastructure challenges, such as inadequate classrooms and outdated teaching materials (Harahap et al, 2023;Idris et al, 2023). Understanding how these conditions impact academic achievement is critical to developing targeted interventions to meet the unique needs of students in rural areas (Tripon et al, 2023).…”
Section: Educational Facilities and Academic Performancementioning
confidence: 99%
“…Moral and religious development also affects children's emotional intelligence. Children who can control themselves and easily show empathy and compassion will easily socialize with people around them, especially with their friends (Idris, Willya, Mokodenseho, & Musthan, 2023).…”
Section: Early Childhood Social-emotional Developmentmentioning
confidence: 99%